1997
DOI: 10.1002/art.1780400519
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the incidence and severity of collagen‐induced arthritis in DBA/1 mice, using exogenous dehydroepiandrosterone

Abstract: Objective. This study examined the effect of exogenous dehydroepiandrosterone (DHEA) on the onset, incidence, and severity of collagen-induced arthritis (CIA).Methods. DHEA was administered subcutaneously prior to arthritis induction in DBN1 mice, and the severity of the subsequent arthritis was monitored. Serum levels of total IgG and IgG isotype-specific anti-murine type I1 collagen were measured.Results. Repeated administration of DHEA during arthritis induction delayed the onset and decreased the severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 15 publications
(14 reference statements)
1
22
0
Order By: Relevance
“…Low levels of DHEA in patients with rheumatoid arthritis (RA) have been reported (Wilder, 1996;Cutolo, 2000;Kanik et al, 2000), along with suggestions that replacement therapy could provide benefit. DHEA showed benefit in animal models of RA, including the DBA mouse model of collagen-induced arthritis (CIA) (Williams et al, 1997;Kobayashi et al, 2003;Röntzsch et al, 2004). However, in carefully controlled clinical trials, DHEA treatment produced only modest benefits and unwanted side effects (Giltay et al, 1999;van Vollenhoven, 2000).…”
mentioning
confidence: 99%
“…Low levels of DHEA in patients with rheumatoid arthritis (RA) have been reported (Wilder, 1996;Cutolo, 2000;Kanik et al, 2000), along with suggestions that replacement therapy could provide benefit. DHEA showed benefit in animal models of RA, including the DBA mouse model of collagen-induced arthritis (CIA) (Williams et al, 1997;Kobayashi et al, 2003;Röntzsch et al, 2004). However, in carefully controlled clinical trials, DHEA treatment produced only modest benefits and unwanted side effects (Giltay et al, 1999;van Vollenhoven, 2000).…”
mentioning
confidence: 99%
“…15,16) Moreover, Williams et al reported that administration of exogenous DHEA to DBA/1J CIA mice prevented the development of CIA. 42) Taking these findings into account, the retention of DHEA on day 28 and day 48 in CIA mice may be the result of the physiological response in protection against CIA.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies support the view that DHEA and DHEAS are decreased in rheumatoid arthritis and SLE [16, 17]. Therapeutic compensation of this deficit by DHEA supplementation seems to have beneficial effects in these clinical conditions as well as in related animal models [18, 19, 20]. In line with these immunological effects are reports that DHEA can also influence the regulation of the Th1/Th2 balance and has inhibitory effects on the secretion of cytokines such as IL-6 in vivo and TNF-α in vitro [21, 22].…”
Section: Introductionmentioning
confidence: 85%